2020
DOI: 10.3390/min10090796
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Stiffness, and Microstructure of Wood-Ash Stabilized Marine Clay

Abstract: The world’s population is growing at a rapid pace, thus increasing the need for shelter, which, because of increased carbon emissions, is making our planet less habitable. Thus, supplementary cementitious materials (SCMs) are used to reduce the embodied carbon emissions in the building sector. Wood-ash, as a replacement for cement in ground improvement, seems to be a promising material. In this study, we considered the strength, stiffness, and microstructural behavior of marine deposited clays of Cyprus treate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Typical XRD pattern wood ash [7] Fig. 4 illustrate SEM analysis of SDA as angular, brittle, and elongated granules with jagged edges of SDA from [11]. 4 Saw dust ash application Some research for applications of SDA utilization in road construction has been conducted in few past years.…”
Section: Statement Of Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical XRD pattern wood ash [7] Fig. 4 illustrate SEM analysis of SDA as angular, brittle, and elongated granules with jagged edges of SDA from [11]. 4 Saw dust ash application Some research for applications of SDA utilization in road construction has been conducted in few past years.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…The industrial output of a wood manufacturing plant produces a variety of by-products. One of the majors is saw dust ash, produced when residue from wood chips, bark, sawdust, and cuts is used as an energy source [11]. The yearly production of saw dust ash is around 10,000 tons, but with increased production, the amount is approximately double.…”
Section: Introductionmentioning
confidence: 99%
“…The use of coal or biomass fly ash in concrete reduces the consumption of natural resources and reduces the CO 2 emissions caused primarily through the reduction of Portland cement content in concrete [ 19 ]. Besides in the concrete industry, it has been shown that fly ash finds its application in various construction areas [ 20 , 21 , 22 , 23 , 24 , 25 ]. Pulverized coal fly ash has gained considerable importance as a supplementary cementitious material due to its pozzolanic properties, but also due to the improved workability of concrete attributed to the spherical shape and plain surface of ash particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the properties of high moisture content, high porosity and low strength in natural state of soft soil, it cannot be used directly as subgrade or foundation and is difficult to be recycled as building materials [1][2][3]. Adding suitable binders into soft soil is considered to be a very useful way to solve the above significant engineering problems and has been widely used [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%